Mask Usage and Handling of Face Mask in Rural Health and Training Center - Thamarai Selvi Jayakumar; A. Meriton Stanly (Wolters Kluwer Medknow Publications, 2024)
Background: The mask is defined as a cloth mask, medical mask, and N95 respiratory worn over the face, covering the bridge of the nose, mouth, and chin. Correct use of masks is essential. Mask usage is an important concern when visiting high-risk area as hospitals where the risk of cross-contamination is predominant. The objective of the study was to estimate the prevalence of mask usage among patients attending the Rural Health and Training Center (RHTC). The aim of this study was to assess the association of mask usage with sociodemographic factors among patients attending RHTC and to determine the handling of face masks among patients attending RHTC. Methods: The study was directed to 287 patients in the outpatients. Using a semi-structured questionnaire, sociodemographic characteristics and mask usage details were collected from the study participants. Results: The prevalence of mask usage was 68.3%. The usage of mask was significantly higher among females (OD = 1.383, 95% confidence interval [CI] =0.836-2.286, P = 0.206), younger individuals (OD = 2.569, 95% CI = 1.423-4.636, P = 0.206), literate individuals (OD = 4.073, 95% CI = 2.040-6.892), employed (OD = 2.256, 95% CI = 1.292-3.940, P = 0.013), and upper and middle socioeconomic class (OD = 3.764, 95% CI = 2.219-6.385, P = 2.219-6.385). Handling of face mask with proper wearing and disposal were 18.5% and 25.1%, respectively. Conclusion: The prevalence of mask usage was observed to be 68.3%. The study results emphasize that mask usage is a primordial prevention and mode of intervention as health education and specific protection in the general population would necessarily improve compliance and flatten the epidemiological curve.